Desenvolvimento de projeto para modernização do laboratório de mecânica dos fluídos da Faculdade de Engenharia de Guaratinguetá - Brito, Arthur Bianchi Benedicto [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
This work presents an analysis of the current facilities of the Fluid Mechanics Laboratory of the Faculty of Engineering of Guaratinguetá, considering previously defined criteria. After this step, different possibilities for improvements and available technologies were listed, which were later evaluated again using specific criteria. After the evaluation of the options and with the help of suppliers and manufacturers, the components were budgeted, with the objective of pricing the individual improvement of each bench, as well as the whole installation, including the necessary infrastructure. For items for which a real proposal was not possible, an estimate was made based on similar situations. At least, after being compiled, the values were displayed and final considerations were made in order to guide the acquisitions, taking into account the benefits that each one of them can bring to the laboratory as a whole.

Neste trabalho é apresentada uma análise das atuais instalações do Laboratório de Mecânica dos Fluidos da Faculdade de Engenharia de Guaratinguetá, considerando critérios previamente definidos. Após esta etapa, foram elencadas diferentes possibilidades de melhorias e tecnologias disponíveis, que posteriormente, foram avaliadas novamente se utilizando de critérios específicos. Após a avaliação das opções completas e com auxílio de fornecedores e fabricantes, os componentes foram orçados, com o objetivo de precificar a melhoria individual de cada bancada, bem como da instalação como um todo, incluindo a infraestrutura necessária. Para os itens, dos quais não foi possível uma proposta real, foi feita uma estimativa baseada em situações semelhantes. Por último, depois de compilados, os valores foram exibidos e as considerações finais foram feitas visando nortear as aquisições, levando em conta os benefícios que cada uma delas pode trazer para o laboratório como um todo.
Development of a project for modernization of fluid mechanics laboratory of Engineering School of Guaratinguetá
Keywords: Laboratory; Fluid mechanics; Modernization; Experiments; Pumps; Instrumentation; Laboratório; Mecânica dos fluidos; Modernização; Experimentos; Bombas; Instrumentação; Laboratórios de engenharia; Planejamento experimental